2005
DOI: 10.1096/fj.04-3508fje
|View full text |Cite
|
Sign up to set email alerts
|

Role of tissue kallikrein in the cardioprotective effects of ischemic and pharmacological preconditioning in myocardial ischemia

Abstract: Tissue kallikrein (TK), a major kinin-forming enzyme, is synthesized in the heart and arteries. We tested the hypothesis that TK plays a protective role in myocardial ischemia by performing ischemia-reperfusion (IR) injury, with and without ischemic preconditioning (IPC) or ACE inhibitor (ramiprilat) pretreatment, in vivo in littermate wild-type (WT) or TK-deficient (TK-/-) mice. IR induced similar infarcts in WT and TK-/-. IPC reduced infarct size by 65% in WT, and by 40% in TK-/- (P<0.05, TK-/- vs WT). Ramip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
80
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 43 publications
10
80
2
Order By: Relevance
“…This compensatory phenomenon is also observed by other researchers in mouse models. 18,22,23 The exact role of the B1R in the diabetic kidney warrants further investigation. Apart from biochemical improvement, there was also histological improvement, and reduced macrophage infiltration and interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…This compensatory phenomenon is also observed by other researchers in mouse models. 18,22,23 The exact role of the B1R in the diabetic kidney warrants further investigation. Apart from biochemical improvement, there was also histological improvement, and reduced macrophage infiltration and interstitial fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Intact kinins bind to the kinin B2 receptor and activate second messengers such as nitric oxide (NO), cGMP, prostacyclin and cAMP, to produce a broad spectrum of biological effects [10]. A study using kallikrein-or kinin B2 receptor-deficient mice showed that both tissue kallikrein and the B2 receptor play an important role in cardioprotection during ischemic injury [11]. Moreover, a recent report demonstrated that expression of tissue kallikrein in transgenic mice reduces intramyocardial inflammation and oxidative stress in experimental diabetic cardiomyopathy [12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several studies have suggested that agonism of the B1R may have opposite effects from agonism of the B2R on the severity of I/R injury (23). Although expression of the B1R is much less than that of B2R in the kidney and heart of WT mice, it is markedly induced in B2R-null mice (14,15), and expression of both receptors increases in I/R injury (24). However, whether they act synergistically or antagonistically and whether or not the kallikrein-kinin system has net protective effects in I/R injuries remain unanswered questions.…”
mentioning
confidence: 99%